The Impact of Internal Control, Human Resource Competence, and Information System Implementation on Financial Management Effectiveness in Hospitals - Cucu Kurniasih; Rima Rachmawati (Dinasti Publisher, 2025)
This study aims to analyze the influence of internal control systems, human resource competence, and information technology implementation on the effectiveness of financial management at Bandung District Public Hospitals (RSUD). A quantitative method was applied using a survey approach with questionnaires distributed to 64 respondents, including finance staff, data entry personnel, and system operators. Data processing using multiple linear regression method with the help of SPSS software. The results of the study indicate that the internal control system and HR competency have a significant positive impact on the effectiveness of financial management. In contrast, the implementation of information technology through the Hospital Management Information System (SIMRS) does not show a significant impact. These findings suggest that effective financial management is more strongly influenced by internal control quality and individual capability rather than by the mere presence of information systems. The adjusted R square value of 0.829 indicates that the three independent variables explain 82.9% of the variation in financial management effectiveness. This research highlights the importance of strengthening human resource competence and implementing effective internal control systems in hospital financial management. Furthermore, optimizing the use of information technology is necessary to enhance its contribution to financial performance.